Corporate insolvency law : perspectives and principles / Vanessa Finch. - Finch, Vanessa (Cambridge University Press, 2002)
Vanessa Finch provides an interesting look at corporate insolvency laws and processes. She adopts an interdisciplinary approach to place two questions at the centre of her discussion. Are current UK laws and procedures efficient, expert, accountable and fair? Are fundamentally different conceptions of insolvency law needed for it to develop in a way that serves corporate and broader social ends? Topics considered in this wide-ranging book include different ways of financing companies, causes of corporate failure and prospects for designing rescue-friendly processes. Also examined are alternative asset distribution of failed companies, allocations of insolvency risks and effects of insolvency on a company's directors and employees. Finch argues that changes of approach are needed if insolvency law is to develop with coherence and purpose. This book will appeal to academics and students at advanced undergraduate and graduate level, and to legal practitioners throughout the common law world.